Sweet Crave Cinnabuns / Siti Nur Ayuni Tamsir and Siti Nur'aishah Saiful Mazdi - Tamsir, Siti Nur Ayuni; Saiful Mazdi, Siti Nur'aishah (2022)
Sweet Crave Cinnabuns is a partnership business that focuses on online businesses selling bakery and pastry products that will make you crave even more. Sweet Crave Cinnabuns are based on the social media platform to take an order and deliver directly to customers. Basically, we provide baked goods and services by selling cakes and pastries which provide great customer satisfaction. Our products are made from high-end ingredients and fully home-made, as well as to ensure the preparation and sale of bakery products that do not contain additives that are byproducts of prohibited items. Outside of sales, we also provide interesting facts and nutrients for the products we use, as we are very concerned about the ingredients, we use to ensure quality and delicious taste for everyone to enjoy. At Sweet Crave Cinnabuns, we have produced a pastry product which is a cinnamon roll that has four types of flavours with various toppings and produce a new bakery product which is cake, or we name it as "Cinnacakes" on our menu. Prices depend on size, decorations, toppings and bulks. However, we offer affordable prices for anyone who can afford to buy and taste our products. Our marketing strategy is to highlight the quality and value of our products and services. Furthermore, we fully utilise online platforms to promote, market and sell products. This has helped save many of the costs involved and can achieve a broad target market as we use hard selling and soft selling techniques in our marketing strategy. From a customer perspective, they give positive reviews about the product and make them become very addicted and once eaten, they will never be able to stop and it becomes their favourite. We also offer a cash delivery service according to the location provided. It is suitable for customers who want to make a surprise, customers who want to send to colleagues, family and so on. By developing the right marketing methods, we ensure that our business can grow and engage potential customers in our products.